Mg/Ca ratio of Planulina wuellerstorfi and isotopic composition of seawater from IODP Site 363-U1482 - Yixin Chen; Jian Xu; Jun Liu; Tiegang Li; Zhifang Xiong; Peng Zhang; Hong Yan (PANGAEA, 2024)
We present our work on a total of 1368 sediment samples spanning the past ~3.17–1.07 Ma from Site U1482 (15°3.32?S, 120°26.10?E, water depth of 1466m), which was drilled during the International Ocean Discovery Program Expedition 363 in the Timor Passage, the main exit of the Indonesian Throughflow to the Indian Ocean.Here we present benthic Mg/Ca ratios of Planulina wuellerstorfi during ~2-1.07 Ma. Together with the Mg/Ca-temperature calibration , oxygen isotopic composition of seawater (δ18Oseawater) and δ18Oresidual derived from benthic foraminiferal Mg/Ca ratios and benthic δ18O.